EP618 The use of preoperative imaging in endometrial cancer: are ontario physicians following GOC guidelines?. (1st November 2019) - Schnarr, K; Seow, H; Elit, L; Pond, G; Helpman, L; O'Leary, E; Kong, I
Abstract : Introduction/Background: Joint SOCG-GOC-SCG clinical practice guidelines recommend against preoperative imaging studies (such as CT), except for cases of locally advanced disease or aggressive histologies. This study utilized population-based data to evaluate the use of preoperative imaging in Ontario and factors associated with its use. Methodology: Ontario women diagnosed with endometrial cancer from 2006–2016 were identified from the Ontario Cancer Registry. Patients with a hysterectomy prior to the date of diagnosis, non- epithelial histology or a prior cancer diagnosis within 5 years were excluded. Age-standardized incidence rate of endometrial cancer and preoperative imaging (CT or MRI) rates were calculated over time. Predictive factors for preoperative imaging use were determined using multi-variable analysis. A subanalysis was performed on low-risk patients, to determine if preoperative imaging use differed in this population. Results: 21641 cases were included for analysis. From 2006–2016, the number of cases of endometrial cancer increased 48.0%, and age-standardized incidence rate increased 17.6%. The use of preoperative imaging increased from 19.3% to 32.6%. In a subanalysis of a low-risk population, the rate of preoperative imaging was 16%, compared with 26.8% in the combined population. Factors most predictive of preoperative imaging were: non-endometrioid histology, higher stage, higher grade, comorbidity score and rurality score. Conclusion: Endometrial cancer incidence and the use of preoperative imaging has increased from 2006–2016 in Ontario. Guideline compliance was moderate; while preoperative imaging use was associated with high risk features, inappropriate use was still seen in the low risk population. Disclosure: Nothing to disclose.